The exhibition structure and its impact towards visitors' understanding at a museum / Nur Afni Halil ... [et. al] - Nur Afni, Halil; Hashima Mohaini, Mohammad; Nor Ez-zatul Hanani, Rosli; Audrey, John (Universiti Teknologi MARA, Perak, 2018)
The museum relationship with the public has evolved. Back then, the architecture grandeur of museums and its collections; existed in their own sphere; serving only as gatekeeper to history, heritage and culture. However, museum has travelled in term of development and services, from 'cabinets of curiosities' to an institution that communicates through their product which are meaningful, stimulating and, above all, relevant to today's visitors. Today as public expectation of museums changes, museums now take additional roles in the community. While continuing to collect, catalogue, preserve and study its collection, museums have now become an influential institution in generating and transferring of knowledge. They must enrich community life by making their collections accessible, useful and provide a space for interaction and knowledge exchange. In facing these positive developments and changes, there are bigger challenges that museums today have to face. One major challenge is their ability to attract, create curiosity and entertain visitors. There is an important need to initiate interesting exhibition and programs that are relevant, innovative and fun so that visitors' experience is enhanced. Complementary to this, elements such as exhibition structure which can help in facilitating the visitors understanding the message has yet to be proven. Therefore, the Shannon and Weaver model will be used to measure the effectiveness of exhibition structure towards visitors understanding and its impact towards the exhibition. Through quantitative method, survey questionnaire will be distributed to 364 random visitors in Islamic Arts Museum Malaysia. The five-point type scale adopted to measure the exhibition structure which can lead the museum to convey their intended messages successfully to the visitors.